Atividades didáticas de física mediadas por hipermídia: potencialidades para o desenvolvimento da flexibilidade cognitiva - Vidmar, Muryel Pyetro (2017)
The main objective of this research is to investigate to what extent the structuring of didactic activities of Physics based on the assumptions of the Cognitive Flexibility Theory and mediated by hypermedia contribute for potentialize the development of thematic criss-crossing by high school students. We use as research conception the action-research, in which are developed cycles characterized by momentspotentialize of planning, action, observation and reflection. In this sense, the planning moment of action-research consisted in the elaboration of didactic activities of Physics structured based on the assumptions of the Cognitive Flexibility Theory. These activities were mediated technologically by hypermedia educational resources and treate of the physical knowledges associated with thematic electric energy in the homes. In the moments of action and observation of action-research, these didactic activities were implemented with students from third grade of high school of a state public school, located in the city Santa Maria – RS. To finish, at the moment of reflection, we evaluated the didactic activities implemented through the analysis of the student's resolution to the activities, with a focus on the main objective of the research. The results obtained allowed us to conclude that the structuring of didactic activities of Physics, based on the assumptions of the Cognitive Flexibility Theory and mediated by hypermedia, contribute for potentiate the development of thematic criss-crossing by students, essential for the development of cognitive flexibility. This is because this structuring made possible them to adequately develop the fundamental aspects of these criss-crossings, associated with deconstruction and reconstruction of concepts: analysis of mini cases and cases according to the associated conceptual analysis themes; and criss-crossing in mini cases to understand how a certain theme applies in distinct cases and mini cases.